In situ XPS characterisation of VPO catalyst; XVI International Conference on Chemical Reactors CHEMREACTOR-16, Berlin, Germany, December 1-5, 2003 - Kleimenov E.; Bluhm H.; Hävecker M.; Knop-Gericke A.; Pestryakov A. N. Aleksey Nikolaevich; Teschner D.; Hutchings G. J.; Lopez-Sanchez J. A.; Bartley J. K.; Schlögl R. (2003, 2003)
В фонде НТБ ТПУ отсутствует